Faktor-Faktor Yang Mengembangkan Kreasi Produk pada Ina Priyono The Muslim Wear - Devvy Listiyani Putri; Hari Susanta Nugraha (Universitas Diponegoro, 2017)
This research was to identify and describe the factors to develop of product creation in Ina Priyono The Muslim Wear. This research is a qualitative descriptive study by collecting data through interview and document study. Informants were collected is owner, supplier, consumen, and some employees. In this study, researcher used the factor creative person, creative task, organizational context, environment and product innovation. The results obtained is creative person in Ina Priyono The Muslim Wear still not optimal. It is known through research that show the factor to develop the product creation that is an motivation has been good, but to talent and competence still weak.. The advices given by the researcher is about to improve competence by providing specific training on a legular basis. Creative task still not optimal too, seen from work and enterpreunership are bad, although the leadership is done well. The advices given is company need to develop job description more clearly and need to take into account market orientation. Organizational context still not optimal. This is known from the bad performance of the company. The advices given by the researcher is about to repaired corporate structure, because this affects the company’s performance in producing innovation products. Environment not optimal, seen from companies are less sensitive in response to competition. The advices given is company need to respond positively of competition, as competition has an effect. Product innovation still not optimal., it is known from less of waste utilization. The advices given by the researcer is about to professional handling within waste utilization.